Word of Mouth (Wom) Ability and Accessibility Increasing the Number of Tourism Visits (Case Study of Tibrena Sibolangit) - Dewi Nurmasari Pane; Breyma Baharudin Maulana Tarigan (Junal Ilmu Manajemen, 2022)
This research is a quantitative study that aims to determine whether interest in visiting, word of mouth and accessibility influence partially or simultaneously on increasing the number of tourist visits in Tibrena Sibolangit. The population in this study are all visitors who come to Tibrena Sibolangit. The number of samples is 96 respondents. The results of the research and data processing show that word of mouth partially has a positive and significant effect on increasing tourist visits to Tibrena Sibolangit. Word of mouth and accessibility simultaneously have a positive and significant effect on increasing tourist visits in Tibrena Sibolangit with an F count of 24.324 with a significant level of 0.000.